An ultrasonic-assisted soft abrasive flow processing method for mold structured surfaces. (January 2019) - Li, Jun; Zhu, Fangming; Yu, Junyang
As a fluid-based precise processing method, soft abrasive flow processing has been widely used in advanced electromechanical systems, complex mold manufacturing, and other engineering fields. Because of the low volume fraction of abrasive particles and micro-force/cutting removal characteristics, there exists a potential improvement in terms of processing efficiency and uniformity. In view of the above problems, this article presents an ultrasonic-assisted soft abrasive flow processing method. Based on the realizable k–ε turbulence model and the mixture flow model, an ultrasonic coupling enhancement dynamic model for soft abrasive flow is set up, and the kinetic energy transport equation of realizable k–ε turbulence model can be revised. Using particle image velocimetry technology, an on-line observation experimental platform for ultrasonic-assisted soft abrasive flow is developed to conduct the real-time acquisition of abrasive flow state and particle distribution in a constrained flow passage. An ultrasonic-assisted soft abrasive flow processing experimental platform is established to complete the processing experiment. The experimental results show that the ultrasonic excitation vibration can effectively enhance the turbulence intensity and distribution uniformity of the abrasive flow, the average processing time can be shortened by more than 6 h, and a better surface quality can be obtained.